Uncompromising Affirmation of Culture: Soyinka’s Death and the King’s Horseman - Khanal, Nagarjun (Tribhuvan University Journal, 2010)
Whole Soyinka’s Death and the King’s Horseman is the convergence of two issues: the first focuses on the Yoruba priest Elesin, who represents the embodiment of the mythology and the history of the people; the second concentrates on the “sterile, existential wasteland” (Ralph-Bowman, 1983) of the white colonialists. The two issues come into conflict in the sacrifice of Elesin’s European-educated son, Olunde, whose death represents a significant and uncom promising affirmation of Yoruba cultural tradition. The sacrifice ofolunde, though appears as metaphysical, is entirely secular and practical. Hedies to preserve the safety of his community and his action can be appreciated as a form of martyrdom. Olunde’s sacrifice symbolizes an act that asserts the value of higher duty against both the internal threat of materialistic self-interest and the external threat of an imposed alien culture.